2020
DOI: 10.5194/bg-17-2553-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ocean carbonate system variability in the North Atlantic Subpolar surface water (1993–2017)

Abstract: Abstract. The North Atlantic is one of the major ocean sinks for natural and anthropogenic atmospheric CO2. Given the variability of the circulation, convective processes or warming–cooling recognized in the high latitudes in this region, a better understanding of the CO2 sink temporal variability and associated acidification needs a close inspection of seasonal, interannual to multidecadal observations. In this study, we investigate the evolution of CO2 uptake and ocean acidification in the North Atlantic Sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 105 publications
(195 reference statements)
3
27
0
Order By: Relevance
“…In this study, the DIC/TA dataset revealed a significant increase in DIC concomitant with a somewhat unexpected increase of TA at the two nearshore stations and relatively stable TA at SOMLIToffshore during the study period (Figure 5). Recent observations based on similar DIC/TA datasets also revealed an increase in TA for the 2007-2015 period, albeit in very different ecosystems at the coastal Point B site in the Mediterranean Sea (Kapsenberg et al, 2017) and in the North Atlantic Subpolar Gyre (Leseurre et al, 2020). In our study, similarly, to the observations made at point B and contrary to the North Atlantic Subpolar Gyre, the increase in TA was concomitant with a significant increase in pCO 2 of 3.52 ± 0.47, 2.95 ± 1.04, and 3.11 ± 0.49 µatm year −1 and decrease in pH of −0.0029 ± 0.0005, −0.0028 ± 0.0010, and −0.0027 ± 0.0004 year −1 at SOMLIT-Brest, SOMLIT-pier, and SOMLIT-offshore, respectively (Figure 5).…”
Section: Deconvolution Of Carbonate System Trends During the 2008-2017 Periodmentioning
confidence: 73%
See 4 more Smart Citations
“…In this study, the DIC/TA dataset revealed a significant increase in DIC concomitant with a somewhat unexpected increase of TA at the two nearshore stations and relatively stable TA at SOMLIToffshore during the study period (Figure 5). Recent observations based on similar DIC/TA datasets also revealed an increase in TA for the 2007-2015 period, albeit in very different ecosystems at the coastal Point B site in the Mediterranean Sea (Kapsenberg et al, 2017) and in the North Atlantic Subpolar Gyre (Leseurre et al, 2020). In our study, similarly, to the observations made at point B and contrary to the North Atlantic Subpolar Gyre, the increase in TA was concomitant with a significant increase in pCO 2 of 3.52 ± 0.47, 2.95 ± 1.04, and 3.11 ± 0.49 µatm year −1 and decrease in pH of −0.0029 ± 0.0005, −0.0028 ± 0.0010, and −0.0027 ± 0.0004 year −1 at SOMLIT-Brest, SOMLIT-pier, and SOMLIT-offshore, respectively (Figure 5).…”
Section: Deconvolution Of Carbonate System Trends During the 2008-2017 Periodmentioning
confidence: 73%
“…These trends were also close to values previously reported at several coastal observatories, such as in the Irminger Sea (−0.0026 ± 0.0006 year −1 ), in the Cariaco Basin (−0.0025 ± 0.0004 year −1 ) (see review of Bates et al, 2014), or in the Mediterranean Sea at Point B (−0.0028 ± 0.0003 year −1 ) (Kapsenberg et al, 2017), although care must be taken when comparing such diverse ecosystems. The North Atlantic trends ranged from −0.0013 ± 0.0009 year −1 (period 1995-2013, Kitidis et al, 2017) to −0.0017 year −1 (period 1993-2017, Leseurre et al, 2020). In open ocean regions of the northern hemisphere, pH trends have been observed concomitantly with sea surface pCO 2 increases close to the atmospheric CO 2 forcing (Kitidis et al, 2017;Wang et al, 2017;Leseurre et al, 2020).…”
Section: Comparison Of Oa Trends and Climatic Context Over The 1997-2020 Periodmentioning
confidence: 95%
See 3 more Smart Citations